Effects of Acid Washing and Additives on Qualities of Waste Lubricating Oil - Haque, M Naimul; Miah, M Yunus; Ashruf, S Ali; Islam, M Rafiqul; Das, A Kumar (Bangladesh Journal of Scientific and Industrial Research, 2009)
Waste lubricating oil has been reclaimed by treatment with commercial sulphuric acid followed by adsorption on fuller's earth. A maximum yield (75%) of reclaimed oil at acid- oil ratio of 10:100 with addition of 10% (w/v) fuller's earth has been obtained. Properties of reclaimed oil such as viscosity index, pour point, colour etc. have been improved from 93.4, +2, 5.0 to 109, -10.5, 4.0 by addition of certain proportion of additives. TGA analysis of waste lubricating oil, reclaimed oil and fresh lubricating oil has also been studied. The reclaimed oil obtained after addition of different types of additives is very comparable to SAE 30 grade lubricating oil in terms of properties and is applicable as a standard lubricant. Such a reuse of waste lubricating oil, in addition to its economic effect will help to reduce environmental problem. Key words: Lubricating oil, TGA analysis, Envirormentl problem and Vscosity index. doi: 10.3329/bjsir.v43i4.2243 Bangladesh J. Sci. Ind. Res. 43(4), 529-536, 2008